2012
DOI: 10.1128/iai.06018-11
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Natural Killer T Cells in Patients with Active Mycobacterium tuberculosis Infection

Abstract: d Natural killer T (NKT) cells are known to play a protective role in the immune responses of mice against a variety of infectious pathogens. However, little is known about the detailed information of NKT cells in patients with Mycobacterium tuberculosis infection. The aims of this study were to examine NKT cell levels and functions in patients with active M. tuberculosis infection, to investigate relationships between NKT cell levels and clinical parameters, and to determine the mechanism responsible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 46 publications
5
59
1
Order By: Relevance
“…Barcelos et al [20] found that patients have a higher percentage of CD56 þ CD3 þ than infected controls, and Kulpraneet et al [19] showed that in PBMCs cultures stimulated with mycobacteria, TB patients had a greater percentage of IFN-g producing NKT cells compared to controls. In pulmonary and extrapulmonary TB patients, invariant NKT cells have a decreased proliferative capacity in response to a-GalCer, compared with latent infected individuals and healthy controls [38]. Our results also show that, regardless of BCG vaccination and antigen used (PPD or CFP-10), PTB and TSTþ HHC have a greater percentage of CD56 þ CD3 þ CD69 þ proliferating precursors and IFN-g producers compared to TSTÀ Non HHC, who showed a negligible responses.…”
Section: Discussionsupporting
confidence: 58%
“…Barcelos et al [20] found that patients have a higher percentage of CD56 þ CD3 þ than infected controls, and Kulpraneet et al [19] showed that in PBMCs cultures stimulated with mycobacteria, TB patients had a greater percentage of IFN-g producing NKT cells compared to controls. In pulmonary and extrapulmonary TB patients, invariant NKT cells have a decreased proliferative capacity in response to a-GalCer, compared with latent infected individuals and healthy controls [38]. Our results also show that, regardless of BCG vaccination and antigen used (PPD or CFP-10), PTB and TSTþ HHC have a greater percentage of CD56 þ CD3 þ CD69 þ proliferating precursors and IFN-g producers compared to TSTÀ Non HHC, who showed a negligible responses.…”
Section: Discussionsupporting
confidence: 58%
“…In recent reports, PD-1 and its ligands have been implicated in the induction and maintenance of T cell and NKT cell anergy (37,38,42,43). In our previous report, we demonstrated that NKT cell dysfunction was associated with upregulation of inhibitory receptor PD-1 in active tuberculosis, and it was partially recovered by blockade of PD-1 (44). In this study, we investigated the relevance of PD-1 expression to MAIT cell dysfunction in SLE and RA.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in the frequencies of iNKT cells has been reported in pulmonary tuberculosis patients. Using antibodies mainly against CD3 and the Vα24 and Vβ11 chains of iNKT cell TCR to identify iNKT cells, some studies have shown a numerical deficiency of iNKT cells in tuberculosis patients [43,44,45,46,47]. However, other studies contradict these findings and report a steady incline in the number of these cells in the peripheral blood [48,49,50,51].…”
Section: Inkt Cells In Immunity To Intracellular Bacterial Infectionsmentioning
confidence: 73%
“…In the case of Brucella suis infection, CD4+CD8- iNKT cells have been found to effectively inhibit bacterial growth and/or kill the bacteria through the production of IFN-γ and cytotoxic activities [55]. Recently, Kee et al [46 ]conducted a detailed analysis of iNKT cells in patients with active M. tuberculosis infection. They found that the number of these cells was lower in the peripheral blood of both pulmonary and extrapulmonary tuberculosis patients when compared to patients with latent tuberculosis and to healthy controls.…”
Section: Inkt Cells In Immunity To Intracellular Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation